Designing transportation for women: Night paratransit service for the female community of Sapienza university of Rome - Maria Vittoria Corazza; Silvia D’Eramo (Transportation Research Interdisciplinary Perspectives)
The local press often reports on women’s harassment in transit, which poses a significant problem for the female community at Sapienza University of Rome, particularly during evening commutes. A dedicated night transport service could serve as a solution. However, research questions revolve around service acceptance and affordability among the so-called “Sapienza women” (female students and teaching and administrative staff), along with service profitability for the university acting as an operator. A feasibility study of a gender-dedicated university-to-home paratransit night service called MinervaMove from Sapienza’s main campus for commuting home in the evening is conducted. The service analyzes the Sapienza Women’s stated preferences to assess its acceptance and willingness to pay for it, followed by building operational scenarios accordingly. A detailed cost–benefit analysis, duly described in the paper, stresses the prospective profitability of MinervaMove, with the research goals to showcase an example of a methodology to design a women-reserved night service, replicable in other university campuses, and advance knowledge in the field of gender-driven transportation supply.